The Role of Remote Work Flexibility, Organizational Justice, and Psychological Safety on Disrectionary Work Behavior - Rama, Rovanita (International Journal of Business, Law, and Education, 2025)
This study examines the role of remote work flexibility, organizational justice, and psychological safety in influencing discretionary work behavior among employees. As organizations increasingly adopt hybrid and remote work models, understanding how workplace flexibility and psychological and structural fairness impact employee behavior beyond formal job descriptions has become essential. Using a quantitative approach, data were collected from a sample of employees across various industries and analyzed using SPSS version 26. Descriptive statistics, reliability analysis, correlation analysis, and multiple linear regression were conducted to explore the relationships among the variables. The results demonstrate that all three independent variables—remote work flexibility, organizational justice, and psychological safety—have a significant positive effect on discretionary work behavior. These findings suggest that organizations that provide flexible work arrangements, uphold fairness, and create psychologically safe environments can encourage employees to exhibit behaviors that benefit the organization beyond their core responsibilities. The implications of this study contribute both theoretically and practically to the fields of organizational behavior and human resource management by offering insights into how non-obligatory employee behaviors can be fostered through supportive work environments.